2015
DOI: 10.1039/c4nr04038d
|View full text |Cite
|
Sign up to set email alerts
|

Use of carbosilane dendrimer to switch macrophage polarization for the acquisition of antitumor functions

Abstract: Tumor microenvironment favors the escape from immunosurveillance by promoting immunosuppression and blunting pro-inflammatory responses. Since most tumor-associated macrophages (TAM) exhibit an M2-like tumor cell growth promoting polarization, we have studied the role of 2G-03NN24 carbosilane dendrimer in M2 macrophage polarization to evaluate the potential application of dendrimers in tumor immunotherapy. We found that the 2G-03NN24 dendrimer decreases LPS-induced IL-10 production from in vitro generated mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…This is concordant with the synergy between TLR2/1L and IFN‐ γ to induce the genes encoding these antimicrobial peptides in monocytes . Hence, re‐polarization of M2 M Φ into M1 M Φ could be a powerful tool in augmenting host defense against intracellular pathogens, as well as to generate antitumor effects …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This is concordant with the synergy between TLR2/1L and IFN‐ γ to induce the genes encoding these antimicrobial peptides in monocytes . Hence, re‐polarization of M2 M Φ into M1 M Φ could be a powerful tool in augmenting host defense against intracellular pathogens, as well as to generate antitumor effects …”
Section: Discussionsupporting
confidence: 53%
“…14 Hence, re-polarization of M2 MΦ into M1 MΦ could be a powerful tool in augmenting host defense against intracellular pathogens, as well as to generate antitumor effects. 26,27 The conversion of M2 MΦ into M1-like MΦ was not only triggered by the addition of TLR2/1L plus IFN-c, but also by the addition of TLR2/1L plus anti-IL-10 neutralizing antibodies. Interleukin-10 has long been known to inhibit MΦ function including cytokine production 28 and antimicrobial function.…”
Section: Discussionmentioning
confidence: 99%
“…Carbosilane dendrimer 2G-03NN24 can cause polarization M2 to M1 polarization, decreasing the expression of several M2-related genes, which, in turn, increases the expression of M1 characteristics. These results were confirmed by functional assays, given the M1-oriented proinflammatory and antitumor responses ( 107 ). The mechanism involved inhibits phosphorylation of STAT3, which boosts the capacity of macrophages to promote cytotoxic response and presentation of tumor antigens ( 107 , 108 ).…”
Section: Introductionmentioning
confidence: 59%
“…These results were confirmed by functional assays, given the M1-oriented proinflammatory and antitumor responses ( 107 ). The mechanism involved inhibits phosphorylation of STAT3, which boosts the capacity of macrophages to promote cytotoxic response and presentation of tumor antigens ( 107 , 108 ). Furthermore, it has been demonstrated that a system composed of gold nanoparticles adapted with MUC-1 protein fragment was capable of promoting macrophage activation and M1 polarization, characterized by increased antigen presentation and M1-like cytokine expression ( 109 ).…”
Section: Introductionmentioning
confidence: 59%
“…The potential applications of anionic dendrimers are very broad, as they could be used as antiviral and antibacterial agents [ 17 , 20 , 21 , 22 , 23 ], as carriers of chemical drugs and peptides [ 24 , 25 , 26 , 27 , 28 ], as gene silencers [ 29 ], and as potential therapeutic agents for diverse pathological conditions, including neurodegenerative diseases (such as Alzheimer´s disease) [ 30 ], cancer [ 31 , 32 , 33 ], chronic inflammatory diseases [ 34 , 35 ] and infectious diseases [ 36 ], among others.…”
Section: Introductionmentioning
confidence: 99%